Tower of 2 Summation

Algebra Level 5

1 + r = 0 10 2 2 r + r 1 1 + 2 2 r = 2 α 2 β 1 \large 1 + \sum_{r=0}^{10} \frac {2^{2^r+r-1}}{1+2^{2^r}} = \frac {2^\alpha}{2^\beta -1}

The equation above holds true for real numbers α \alpha and β \beta . Find α + β + α β \alpha +\beta +\alpha \beta .


The answer is 4218890.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 23, 2018

Let S n = 1 + r = 0 n 2 2 r + r 1 1 + 2 2 r S_n = 1 + \displaystyle \sum_{r=0}^n \frac {2^{2^r+r-1}}{1+2^{2^r}} . First few n n s show that S n = 2 a n 2 b n 1 S_n = \dfrac {2^{a_n}}{2^{b_n}-1} , where a n = 2 n + 1 + n a_n = 2^{n+1}+n and b n = 2 n + 1 b_n = 2^{n+1} . Let us prove the induction that the claim is true for all n 0 n \ge 0 .

Proof: For n = 0 n=0 , S 0 = 1 + 2 2 0 + 0 1 1 + 2 2 0 = 1 + 1 3 = 4 3 = 2 2 2 2 1 S_0 = 1 + \dfrac {2^{2^0+0-1}}{1+2^{2^0}} = 1 + \dfrac 13 = \dfrac 43 = \dfrac {2^2}{2^2-1} . Note that a 0 = 2 0 + 1 + 0 = 2 a_0 = 2^{0+1} + 0 = 2 and b n = 2 0 + 1 = 2 b_n = 2^{0+1} = 2 . Therefore, the claim is true for n = 0 n=0 . Now assuming that the claim is true for n n , then:

S n + 1 = 1 + r = 0 n + 1 2 2 r + r 1 1 + 2 2 r = S n + 2 2 n + 1 + n 1 + 2 2 n + 1 = 2 2 n + 1 + n 2 2 n + 1 1 + 2 2 n + 1 + n 2 2 n + 1 + 1 = 2 2 n + 1 + n ( 1 2 2 n + 1 1 + 1 2 2 n + 1 + 1 ) = 2 2 n + 1 + n ( 2 2 n + 1 + 1 + 2 2 n + 1 1 ( 2 2 n + 1 1 ) ( 2 2 n + 1 + 1 ) ) = 2 2 n + 1 + n ( 2 × 2 2 n + 1 2 2 n + 1 × 2 1 2 ) = 2 2 n + 2 + n + 1 2 2 n + 2 1 = 2 a n + 1 2 b n + 1 1 \begin{aligned} S_{n+1} & = 1 + \sum_{r=0}^{n+1} \frac {2^{2^r+r-1}}{1+2^{2^r}} \\ & = S_n + \frac {2^{2^{n+1}+n}}{1+2^{2^{n+1}}} \\ & = \frac {2^{2^{n+1}+n}}{2^{2^{n+1}}-1} + \frac {2^{2^{n+1}+n}}{2^{2^{n+1}}+1} \\ & = 2^{2^{n+1}+n} \left(\frac 1{2^{2^{n+1}}-1} + \frac 1{2^{2^{n+1}}+1} \right) \\ & = 2^{2^{n+1}+n} \left(\frac {2^{2^{n+1}}+1+2^{2^{n+1}}-1}{\left(2^{2^{n+1}}-1\right)\left(2^{2^{n+1}}+1\right)} \right) \\ & = 2^{2^{n+1}+n} \left(\frac {2\times 2^{2^{n+1}}}{2^{2^{n+1}\times 2}-1^2} \right) \\ & = \frac {2^{2^{n+2}+n+1}}{2^{2^{n+2}}-1} \\ & = \frac {2^{a_{n+1}}}{2^{b_{n+1}}-1} \end{aligned}

Therefore, the claim is also true for n + 1 n+1 implying it is true for all n 0 n\ge 0 .

Therefore, α = a 10 = 2 11 + 10 = 2058 \alpha = a_{10} = 2^{11} + 10 = 2058 , β = b 10 = 2 11 = 2048 \beta = b_{10} = 2^{11} = 2048 and α + β + α β = 4218890 \alpha + \beta + \alpha\beta = \boxed{4218890} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...